What is the quality of drug therapy clinical practice guidelines in Canada? - Graham, Ian D. (2001)
BACKGROUND: The Canadian Medical Association maintains a national online database of clinical practice guidelines developed, endorsed or reviewed by Canadian organizations within 5 years of the current date. This study was designed to identify and describe guidelines in the database that make recommendations related to the use of drug therapy, and to assess their quality using a standardized guideline appraisal instrument. METHODS: Drug therapy guidelines in the database were identified with the use of search terms and hand searching. Descriptive information about the developers, endorsement by other organizations, publication status, disease and drug focus was abstracted. Each guideline was independently assessed by 3 appraisers (a physician, a pharmacist and a methodologist) with the use of the Appraisal Instrument for Clinical Guidelines. Conditions were classified according to the tenth revision of the International Statistical Classification of Diseases and Related Health Problems. RESULTS: We identified 217 drug therapy guidelines produced or reviewed from 1994 to 1998. Guideline developers included national organizations (47.0%), paragovernment organizations (39.6%) and professional associations (30.9%); 31.3% of the guidelines were published, and 10.6% stated drug company sponsorship. The most common conditions addressed by the guidelines were infections and parasitic diseases (39.6%), neoplasms (11.5%) and diseases of the circulatory system (11.5%). Drugs most commonly cited were anti-infective agents (42.9%), antiviral agents (15.2%) and cardiovascular drugs (16.1%). Eleven organizations produced 176 (81.1%) of the guidelines. In all, 14.7% of the guidelines met half or more of the 20 items assessing rigour of guideline development on the appraisal instrument (mean quality score 30.0% [95% confidence interval (CI) 27.5%–32.6%]), 61.8% met half or more of the 12 items assessing guideline context and content (mean score 57.0% [95% CI 54.6%–59.3%]), and none met half or more of the 5 items assessing guideline application (mean score 5.6% [95% CI 4.7%–6.5%]). Overall, 64.6% of the guidelines were recommended with modification by at least 2 of the 3 appraisers, 9.2% were recommended without change, and 26.3% were not recommended. The quality of the guidelines assessed varied significantly by developer, publication status and drug company sponsorship. No substantial improvement in guideline quality was observed over the 5-year study period. INTERPRETATION: Developers of Canadian drug therapy guidelines are producing guidelines that are often perceived to be clinically useful to physicians and pharmacists, although the methods (or the description of the methods) by which they are developed need to be more rigorous and thorough.